Trastornos músculo esqueléticos de origen laboral en las enfermeras/os en el Hospital Regional Isidro Ayora de la ciudad de Loja - Rojas Lima, Jasmín Carolina (2015)
It is difficult to perceive the magnitude of musculoskeletal diseases as part of the physical exertion of any work activity presented by nurses; so this present research work in order to identify musculoskeletal disorders of occupational origin in the nursing staff of the Regional Hospital Isidro Ayora city of Loja, as well as determine the most common site was conducted by anatomical regions; establish working conditions and staff time spent in the workplace, in order to propose a preventive project to help reduce the spread of musculoskeletal discomfort towards improving the well-being, the study is quantitative descriptive, transversal, and it possible to identify and analyze the presence of musculoskeletal and intralaborales conditions in the period January-June 2015 disorders. The instrument used were two surveys for analysis considered all nurses with a sample of 96 nurses of which 91.6% was obtained with pain in the lumbar spine, pain at 87.5% standing and 85 41% calf pain level. These data can be related to conditions such intralaborales; postural risk, monotonous and repetitive work, and additional activities, which increase work-related musculoskeletal symptoms. The results confirm the existence of musculoskeletal disorders, just as there intralaborales conditions that increase the risk and occurrence of musculoskeletal symptoms in nursing personnel. This study will be the starting point for future research, research and monitoring projects; that benefits the entire nursing staff that make up the Regional Hospital "Isidro Ayora". Key.- words Nurses, Working Conditions, back pain, musculoskeletal disorders, Musculoskeletal symptoms.